Developing Performance-based Authentic Assessment Instruments in Learning Productive Marketing of Merchandise Planning Subject (A Study in the Xith Marketing Class in Smkn 1 Turen Kabupaten Malang) - Saputra, E H; Rahayu, W P; Churiyah, M (KnE Social Sciences, 2018)
The purpose of this study and development is to produce products such as performance-based authentic assessment instruments to facilitate teachers to conduct authentic assessment toward process and student learning outcomes in Merchandise Planning subject. This study and development of assessment instruments used R & D Models by Borg and Gall. The stages in the development model of R & D is only up to the fifth stage. The products of development results would be validated by one expert on validation of content, 2 experts on validation of construct, and limited trials on assessment instruments to determine the practicality and readability of the assessment instruments toward 12 students of SMK. The product of the research and the development of development of performance-based authentic assessment instruments on marketing productive learning of merchandise planning is in a printed form. The result of this validation shows that knowledge assessment instruments with eligibility, namely ”eligible”, skills assessment instruments with eligibility, namely ”eligible”, and manner assessment instruments with eligibility, namely ”eligible”. While the validation of construct shows that the knowledge assessment instruments with eligibility, namely ”eligible”, skills assessment instruments with eligibility, namely ”eligible”, and manner assessment instruments with eligibility, namely ”eligible”. The limited trial results have shown that teachers’ responses toward the practicality of the assessment instruments with the criteria of ”easy to use” and for the readability of student worksheet with the criteria of ”easy to use”. Keywords: Assessment Instruments, Authentic, Performance-Based, Marketing, Merchandise Planning